2019
DOI: 10.14744/anatoljcardiol.2019.11456
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with metformin prevents myocardial ischemia-reperfusion injury via STEAP4 signaling pathway

Abstract: Objective: The aim of the present study was to investigate the underlying mechanism of metformin in reducing myocardial apoptosis and improving mitochondrial function in rats and H9c2 cells subjected to myocardial ischemia–reperfusion (I/R) or hypoxia–reoxygenation (H/R) injuries, respectively. Methods: Following pretreatment with metformin, male Sprague–Dawley rats were used to establish an I/R model in vivo. Serum creatinine kinase-MB and cardiac troponin T levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although pharmacotherapy is not commonly included in cardioprotective strategies, several investigations have shown that a number of medicines are capable of cushioning the effects of MI/RI ( 176 , 177 , 179 - 182 , 186 - 190 ). The present review briefly reviews those that promote cell survival and reduce apoptosis by affecting the BCL2/Bax ratio through specific signaling pathways.…”
Section: Therapy Of Mi/rimentioning
confidence: 99%
See 2 more Smart Citations
“…Although pharmacotherapy is not commonly included in cardioprotective strategies, several investigations have shown that a number of medicines are capable of cushioning the effects of MI/RI ( 176 , 177 , 179 - 182 , 186 - 190 ). The present review briefly reviews those that promote cell survival and reduce apoptosis by affecting the BCL2/Bax ratio through specific signaling pathways.…”
Section: Therapy Of Mi/rimentioning
confidence: 99%
“…Metformin, which is widely used for the treatment of carbohydrate metabolism disorders, inhibits apoptosis in culture (H9c2 cells) and rat cardiomyocytes following injury caused by hypoxia-reoxygenation or ischemia-reoxygenation by increasing the BCL2/BAX ratio with the involvement of metalloreductase STEAP4 ( 177 ). These results in vitro and in vivo affirmed the hypothetical effects of metformin on MI/RI produced by cellular apoptosis inhibition.…”
Section: Therapy Of Mi/rimentioning
confidence: 99%
See 1 more Smart Citation
“…Such an effect has been recently reported for the AMP-activated protein kinase (AMPK) activator cilostazol in nonalcoholic fatty liver disease (42). Moreover, in a setting of acute myocardial injury for 2 hours, treatment with the biguanide metformin reduced cardiomyocyte apoptosis in a Stamp2-dependent manner (43). The development of more specific compounds for pharmacological Stamp2 regulation in cardiovascular diseases is therefore an interesting goal for future studies.…”
Section: Discussionmentioning
confidence: 79%
“…Some cardioprotective effects of metformin are mediated for AMPK. This kinase plays an important role in regulating myocardial energy metabolism, and reducing of I/R injury [ 62 , 63 , 64 ]. A recent experimental in vitro study performed by Zhang et al showed that AMPK activation with metformin protected against apoptosis induced by cardiac I/R injury.…”
Section: Cardioprotective Effects Of Metformin On Myocardial I/rmentioning
confidence: 99%